Update on the pathophysiology and therapeutics of chorea disease - Hussein, Riyam; Rayhaan, Suhaila; Abbas, Hawraa Fadhil; Abbas, Hawraa Fadhil; Jasim, Aliaa Ahmed; Hasan, Lina Abbas; Hameed, Rana Majeed; Al-Mousawi, Zainab R. (Pharmakeftiki, 2025)
Chorea is a primary category of involuntary movement disorders arising from aberrant neural circuitry connecting the frontal cortical motor regions and the basal ganglia. Clinically, the syndrome manifests as a high frequency of brief, erratic, and involuntary muscle contractions. Although chorea may result from various aetiologies, the most common contributors include dysregulation of glucose metabolism, thyroid dysfunction, and renal impairment. Neurochemical abnormalities have been implicated in its pathophysiology, notably dysfunction of the presynaptic nigrostriatal dopaminergic pathway, which may lead to increased dopamine turnover. The authors emphasize that the current pharmaceutical armamentarium for chorea remains limited, offering few therapeutic options to clinicians. Tetrabenazine and its derivative, deutetrabenazine, are the principal agents approved by the US Food and Drug Administration specifically for the treatment of chorea associated with Huntington’s disease. This case underscores the persistent and substantial challenges faced by healthcare professionals in managing this complex neurological condition. Further research is urgently warranted in order to expand the therapeutic landscape and to elucidate the pharmacodynamics and pharmacokinetics of existing and emerging agents across diverse patient populations affected by chorea. The objective of this article was to provide a concise overview of the biochemical alterations and pharmacological interventions relevant to chorea.